Common zero point for a finite family of inclusion problems of accretive mappings in Banach spaces. (3rd August 2018) - Chang, Shih-sen; Wen, Ching-Feng; Yao, Jen-Chih
Abstract: The purpose of this article is to propose a splitting algorithm for finding a common zero of a finite family of inclusion problems of accretive operators in Banach space. Under suitable conditions, some strong convergence theorems of the sequence generalized by the algorithm to a common zero of the inclusion problems are proved. Some applications to the convex minimization problem, common fixed point problem of a finite family of pseudocontractive mappings, and accretive variational inequality problem in Banach spaces are presented.